2022
DOI: 10.1177/1934578x221109409
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in silico Evaluation of ACE2 and LOX Inhibitory Activity of Eucalyptus Essential Oils, 1,8-Cineole, and Citronellal

Abstract: Eucalyptus essential oils are well-known and used especially in upper respiratory tract pathologies or diseases as herbal drug preparations. In the present study, the in vitro angiotensin-converting enzyme 2 (ACE2) and lipoxygenase (LOX) enzyme inhibitory potentials of commercial Eucalyptus globulus Labill. and Eucalyptus citriodora Hook. essential oils were evaluated for their potential anti-coronavirus disease 2019 (COVID-19), and anti-inflammatory effects. In addition, the major components, 1,8-cineole and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In the analysis carried out by Sahin Basak e Candan (2013), the major compound found in the essential oil of laurel was also 1,8-cineole (24), however, with a percentage of 68.82%, and the other compounds found were α-pinene (6.94%), and limonene (3.04%). Other studies highlight 1,8-cineole as the major compound in laurel essential oil (AISSAOUI et al, 2023;KARAKOSTA et al, 2022 SAKALLI et al, 2022;AMRI et al, 2023). In the study carried out by Loumouamou et al (2009) six different specimens of E. citriodora essential oil were analyzed, all samples revealed the dominant presence of citronellal (57.1-75.4%) followed by citronellol (8-14.1%) and isopulegol (2.5-5.1%).…”
Section: Resultsmentioning
confidence: 96%
“…In the analysis carried out by Sahin Basak e Candan (2013), the major compound found in the essential oil of laurel was also 1,8-cineole (24), however, with a percentage of 68.82%, and the other compounds found were α-pinene (6.94%), and limonene (3.04%). Other studies highlight 1,8-cineole as the major compound in laurel essential oil (AISSAOUI et al, 2023;KARAKOSTA et al, 2022 SAKALLI et al, 2022;AMRI et al, 2023). In the study carried out by Loumouamou et al (2009) six different specimens of E. citriodora essential oil were analyzed, all samples revealed the dominant presence of citronellal (57.1-75.4%) followed by citronellol (8-14.1%) and isopulegol (2.5-5.1%).…”
Section: Resultsmentioning
confidence: 96%
“…Citronellal was detected in both essential oils (ECB and ECH). The major component of the essential oil of Eucalyptus citriodora is reported as Citronellal in the literature Lee et al, 2008;Ak Sakallı et al, 2022). When the effects of isopulegol and eugenol active substances detected in both essential oils are examined against Eimeria oocysts in vitro, it is known that essential acids are 90% effective against parasitic oocysts even at low doses (Remmal et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It is still unknown if essential oils could play a role in inhibiting the endocytosis of SARS-CoV-2. Enzyme inhibition assay suggests that several essential oils including eucalyptol, menthol, and rosemary oil could inhibit the activity of angiotensin converting enzyme 2 (ACE2) and stipulated to also inhibit the viral entry [ [53] , [54] , [55] ]. Spike protein of SARS-CoV-2 binds to human ACE2, anchored on the surface of cells to gain entry [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis on the keywords from the published literatures revealed that main focus of essential oil research was to investigate the anti -SARS-CoV-2 potential, where most of the studies performed the screening based on ACE2 inhibition [ 35 , [53] , [54] , [55] , 77 ]. Computational simulations, including the most popular one – molecular docking, have become the main modality to screen the antiviral potential of essential oils against SARS-CoV-2 [ [78] , [79] , [80] , [81] , [82] , [83] ].…”
Section: Discussionmentioning
confidence: 99%